Text Message Intervention for Latino Adults to Improve Diabetes Outcomes. (December 2022) - Patton, Sharon R.; Coffman, Maren J.; De Haven, Mark J.; Miller, Cindy; Krinner, Lisa M.
Introduction: Determine the effectiveness of a diabetes text message intervention to improve diabetes outcomes in Latino adults at a free clinic in the southeastern United States.Methods: A pre–post, one-group design was used with a convenience sample ( n  = 24) of Latino adults with type 2 diabetes and A1C ≥ 7 who consented to participate. Over 8 weeks, participants were sent 23 educational and motivational text messages that were based on the American Association of Diabetes Educators (AADE) 7 self-care tasks and the American Diabetes Association (ADA) Standards of Medical Care in Diabetes Mellitus (DM). Diabetes knowledge, self-efficacy, self-care, and A1C were measured.Results: Diabetes knowledge, self-efficacy, self-care, and A1C improved after 8 weeks. Statistically significant results ( p  < .05) were seen in two of the four evaluation instruments administered (Spoken Knowledge in Low Literacy in Diabetes Scale [SKILLD], p  = .001, Diabetes Self-Efficacy Scale [DSES], p  = .000). A1C improvements were significant (0.86 or 10 mmol/mol) from the pre-intervention ( M  = 9.06 [76 mmol/mol], SD  = 1.49) to the post-intervention ( M  = 8.20 [66 mmol/mol], SD  = 1.27, t [23] = 3.02, p  = .006).Conclusion: Personalized communication, education, and follow-up via text messages improved diabetes knowledge, self-efficacy, self-care, and A1C among pilot project participants. Text messages are a useful tool for diabetes management.